Firms' Capital Structure during Crises: Evidence from the United Kingdom - Alhajjeah, Diana; Besim, Mustafa (Mdpi, 2024)
This study was conducted using the dynamic panel two-stage least squares system generalized methods of moments (2SLS-system GMM) to examine how UK companies made capital structure decisions during the COVID-19 pandemic. Contrary to expectations, firms opted to reduce their debt exposure during the pandemic. Tobin's Q was the most significant determinant of capital structure, as it mitigated total debt by 0.25% during the pandemic. This result aligns with the pecking order theory, suggesting that firms prefer internal financing over debt. Simultaneously, combined scores (ESG) and the decomposed environment (E), social (S), and governance (G) scores individually and paired with the COVID-19 dummy negatively affected short-term debt by 0.012%, 0.015%, 0.0068%, and 0.00434%, respectively. This study's results highlight the significance of firms adopting less debt-heavy policies during periods of heightened uncertainty to effectively manage financial risk. This result underscores the importance of prudent financial risk management strategies for navigating the challenges posed by sudden crises. Our findings suggest that a complex interplay of factors influences capital structure decisions during crises, with debt reduction and prudent risk management emerging as critical strategies.
Keywords: capital structure; corporate financial performance; corporate social responsibility; COVID-19